Experimental Study On Mechanical Strength And Performance Of Gigantachola Schortechinii Bamboo (Buluh Semantan) Joints - Rahim, Muhammad Ibrahim Khalili Abd (Universiti Sains Malaysia, 2022)
This study was conducted to investigate the mechanical properties and type of failure mode for various types of Gigantachola Schortechinii bamboo or known as Buluh Semantan joints. In this study, several parameters such as the type of joints, the sample's position, and the sample's angle were examined. The study was carried out on 64 samples, which are orthogonal beam-column, orthogonal beam-beam, angular 30° beamcolumn, angular 30° beam-beam, angular 45° beam-column, and angular 45° beam-beam. While the type of joints consists of a fish mouth, rope and dowel, bolt and nut, dowel, and anchor bolt. The experiment was carried out using Shimadzu Universal Testing Machine (UTM). This test followed the international standard, ISO 22156; Bamboo structures- Bamboo culms- Structural design. The results showed that the traditional joint, fish mouth is the strongest followed by rope and dowel, bolt and nut, dowel, and anchor bolt in every position and condition. From the construction industry perspective, this study is important to introduce bamboo as new and green construction material in Malaysia.